Pengaruh Kualitas Pelayanan dan Kinerja Pegawai terhadap Kepuasan Masyarakat pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bone Bolango - Maimun Ishak; Zuchri Abdussamad; Rusli Isa (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine and analyze the effect of service quality on public satisfaction, the effect of employee performance on public satisfaction, and the effect of service quality on public satisfaction at the Bone Bolango District Population and Civil Registration Office through employee performance. This study uses a quantitative approach with the Partial Least Square (PLS) analysis tool processed using the SmartPLS 4.1 application. The sample in this study consisted of 178 people who applied for services at the Bone Bolango Regency Population and Civil Registration Office. The results of this study are as follows: Service quality significantly influences public satisfaction at the Population and Civil Registration Office of Bone Bolango District, with a T-statistic value (2.961) above the T-table value of 1.96, a P-value of 0.003 below the significance level of <0.05, and an influence coefficient of 0.257 or 25.7%. Employee Performance significantly influences Public Satisfaction at the Population and Civil Registration Office of Bone Bolango District, with a T-Statistic value of 8.832 exceeding the T-Table value of 1.96, a P-Value of 0.000 below the significance level of <0.05, and an influence coefficient of 0.623 or 62.3%. Service quality has a positive and significant impact on public satisfaction at the Population and Civil Registration Office of Bone Bolango District through employee performance, as shown by the Sobel test, with a Z value of 6.16 > 1.96.